2017
DOI: 10.5194/bg-14-2741-2017
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic foraminifera-derived environmental DNA extracted from abyssal sediments preserves patterns of plankton macroecology

Abstract: Abstract. Deep-sea sediments constitute a unique archive of ocean change, fueled by a permanent rain of mineral and organic remains from the surface ocean. Until now, paleoecological analyses of this archive have been mostly based on information from taxa leaving fossils. In theory, environmental DNA (eDNA) in the sediment has the potential to provide information on non-fossilized taxa, allowing more comprehensive interpretations of the fossil record. Yet, the process controlling the transport and deposition o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 52 publications
(73 reference statements)
5
25
0
Order By: Relevance
“…Although earlier studies demonstrated permafrost as one of the best environments for long-term preservation of animal DNA in keratin-and calcium phosphate-based remains, we show here for the first time that permafrost also preserves calcium carbonate-based remains over significant timescales. Past marine diversity was formerly recovered from <43 kyr sediments that yielded DNA from protists, including haptophytes and foraminifera, which are other organisms producing calcium carbonate exoskeletons surviving or dissolving within sediments (Boere et al, 2009;Coolen et al, 2013;Lejzerowicz et al, 2013;Pawłowska et al, 2014;Morard et al, 2017;More et al, 2018;Armbrecht et al, 2019).…”
Section: Preservation Of ≥100 Kyr Dna From Marine Mollusk Shells In Smentioning
confidence: 99%
“…Although earlier studies demonstrated permafrost as one of the best environments for long-term preservation of animal DNA in keratin-and calcium phosphate-based remains, we show here for the first time that permafrost also preserves calcium carbonate-based remains over significant timescales. Past marine diversity was formerly recovered from <43 kyr sediments that yielded DNA from protists, including haptophytes and foraminifera, which are other organisms producing calcium carbonate exoskeletons surviving or dissolving within sediments (Boere et al, 2009;Coolen et al, 2013;Lejzerowicz et al, 2013;Pawłowska et al, 2014;Morard et al, 2017;More et al, 2018;Armbrecht et al, 2019).…”
Section: Preservation Of ≥100 Kyr Dna From Marine Mollusk Shells In Smentioning
confidence: 99%
“…Moreover, it is important to note that recovering DNA directly from sediments without any sieving allows the inclusion of many micro-eukaryotes poorly represented in the databases, thus diminishing assignment success. Not sieving also means that more organismal traces and extracellular DNA are retained, which has the risk of incorporating non-benthic organisms whose DNA has sunk to the bottom [28,77] or even non-marine DNA. It has been said that the deep-sea sediments constitute an archive of present and past marine biodiversity [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…The marine environment is a complex ecosystem in which the distribution of organisms is controlled significantly by abiotic constraints such as sea-surface temperatures (SSTs), salinity, nutrient distribution, light conditions, and sea-ice cover (Cherkasheva et al, 2014;Ibarbalz et al, 2019;Nöthig et al, 2015;Pierella Karlusich et al, 2020). Over the past 30 000 years the subarctic North Atlantic Ocean has been subject to frequent sea-ice expansions and contractions (Müller et al, 2009;Müller and Stein, 2014;Syring et al, 2020;Werner et al, 2013), which are expected to have affected the composition of the regional species pool. Diatoms (Bacillariophyta) are unicellular, siliceous organisms that are photoautotrophic and thrive in the euphotic zone of the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Next to microfossil-based reconstructions, the diatom-produced sea-ice proxy IP 25 (a highly branched isoprenoid alkene with 25 carbon atoms; Belt et al, 2007) combined with phytoplankton biomarkers (e.g. brassicasterol, dinosterol; Volkman, 1986) permit semi-quantitative reconstructions of past sea-ice distribution (Belt, 2018;Belt and Müller, 2013;Müller et al, 2009;Müller and Stein, 2014;Stein et al, 2012Stein et al, , 2017. However, diatoms in northern highlatitudinal regions are less silicified and more prone to silica dissolution (Kohly, 1998;Stabell, 1986) compared to diatoms of the southern polar oceans (Harrison and Cota, 1991).…”
Section: Introductionmentioning
confidence: 99%